Croatian Translators' Take on Swedish Collocations and Idioms - Antunović, Goranka (2007)
A number of linguistic and extralinguistic circumstances seem to counteract the effort that Croatian translators of Swedish texts might be expected to make in order to secure equivalency in both semantic and communicative - including phraseological - value between Swedish lexical phraseological units and their Croatian renderings. In order to establish what the consequences of such circumstances actually are, this study has compared twelve Swedish works of fiction (excerpts from seven and five full texts) with their Croatian translations. In the Swedish texts a number of phraseological units have been identified (201 lemmas, 301 occurrences), classified into collocations, idioms and formulas, and then compared to their translation equivalents (526) established in the Croatian texts. On the basis of such analysis the following answers have been proposed for the questions that have motivated the study: 1. Croatian translators of Swedish fiction tend to recognize the phraseological value of original phraseological units, and make an effort to use a translation equivalent which possesses that same element of communicative value. In the analysed corpus 69.8% of the Croatian equivalents qualify as phraseological units. 2. Translators seem to be better aware of the phraseological value and/or to feel more obliged to render the value of semantically less transparent and structurally more fixed units. In this corpus the number of equivalents that are phraseological units amounts to 63.2% for collocations, 70.2% for idioms, and 94.5% for formulas. 3. At times Croatian translators of Swedish fiction practise literal translation (calquing) of phraseological units. Even if the method can be considered rather risky in terms of the semantic appropriateness of the translation equivalents that it produces, calquing cannot be pronounced the source of failed denotation. It has lead to 22.2% of the equivalents whose denotation does not correspond to that of the original phraseological unit, or the correspondence is questionable. On the other hand, the overall number of such equivalents (with non-matching denotation, obtained either through calquing or some other method) that have been established in the corpus can be deemed relatively high (13.7% of all the analysed equivalents).
Projekt MZOS
ENG